Mitochondrial mistranslation modulated by metabolic stress causes cardiovascular disease and reduced lifespan. Issue 7 (7th June 2021) - Richman, Tara R.; Ermer, Judith A.; Siira, Stefan J.; Kuznetsova, Irina; Brosnan, Christopher A.; Rossetti, Giulia; Baker, Jessica; Perks, Kara L.; Cserne Szappanos, Henrietta; Viola, Helena M.; Gray, Nicola; Larance, Mark; et al.
Abstract: Changes in the rate and fidelity of mitochondrial protein synthesis impact the metabolic and physiological roles of mitochondria. Here we explored how environmental stress in the form of a high‐fat diet modulates mitochondrial translation and affects lifespan in mutant mice with error‐prone ( Mrps12 ep / ep ) or hyper‐accurate ( Mrps12 ha / ha ) mitochondrial ribosomes. Intriguingly, although both mutations are metabolically beneficial in reducing body weight, decreasing circulating insulin and increasing glucose tolerance during a high‐fat diet, they manifest divergent (either deleterious or beneficial) outcomes in a tissue‐specific manner. In two distinct organs that are commonly affected by the metabolic disease, the heart and the liver, Mrps12 ep / ep mice were protected against heart defects but sensitive towards lipid accumulation in the liver, activating genes involved in steroid and amino acid metabolism. In contrast, enhanced translational accuracy in Mrps12 ha / ha mice protected the liver from a high‐fat diet through activation of liver proliferation programs, but enhanced the development of severe hypertrophic cardiomyopathy and led to reduced lifespan. These findings reflect the complex transcriptional and cell signalling responses that differ between post‐mitotic (heart) and highly proliferative (liver) tissues. We show trade‐offs between the rate and fidelity of mitochondrial protein synthesis dictate tissue‐specific outcomes due to commonly encountered stressful environmental conditions or aging. Abstract : This work reveals how trade‐offs between the rate and fidelity of mitochondrial protein synthesis dictate tissue‐specific outcomes to metabolic stress or aging. Error‐prone protein synthesis enhanced the rate of translation, protecting against heart defects but stimulated lipid accumulation in the liver. Enhanced translational accuracy protected liver function through activation of proliferation programs, but resulted in severe hypertrophic cardiomyopathy and reduced lifespan.